Levels of Social Psychological and Socio-Cultural Resilience of Women in Cities Bukittinggi Through Gender Responsive Family Schools - Rahmi, Alfi Rahmi; Mudjiran; Yeni Karneli; Netrawati (Universitas Islam Negeri Madura, 2023)
This study aims to reveal the level of social psychological and socio-cultural resilience of women in the city of Bukittinggi. The vulnerability of families experiencing family resilience problems, so the City Government of Bukittinggi established a Family School. Through the Family School, materials and training are provided for women who have families to maintain the resilience of their families. This type of research is descriptive and quantitative with a total sample of 86 people who have attended the Family School. Data was collected using a Family Resilience questionnaire that had been formulated by the Ministry of Women and Children's Empowerment (KPPA). The results showed that the Dimensions of Psychological Social Resilience with the following categories were Not Resistant 12 people, Sufficiently Resistant 73 people, and Resistant only 1 person. For the Socio-Cultural Dimension, 27 people are Not Resistant, 53 people are Sufficient, and 6 people are Resistant. In general, the level of family resilience in women who have attended Family Schools is Sufficient Level of Having Family Resilience